Meningioma and schwannoma risk in adults in relation to family history of cancer - Hill, Deirdre A. (Duke University Press, 2004)
Relatively little is known about factors that contribute to the development of meningioma and vestibular schwannoma, two intracranial nervous system tumors. We evaluated the risk of these tumors in relation to family history of malignant or benign tumors. Incident cases of meningioma (n = 197) or schwannoma (n = 96) were identified at three U.S. referral hospitals between June 1994 and August 1998. Controls (n = 799) admitted to the same hospitals for nonmalignant conditions were matched to cases on age, sex, race/ethnicity, hospital, and proximity of residence to hospital. We found that risk of meningioma was increased among persons reporting a family history of a benign brain tumor (odds ratio [OR], 4.5; 95% confidence interval [CI], 1.0–21.0; n = 5) or melanoma (OR, 4.2; 95% CI, 1.2–15.0; n = 5). A family history of breast cancer was associated with an elevated meningioma risk among participants aged 18 to 49 years (OR, 3.9; 95% CI, 1.4 –11.0; n = 8) but a reduced risk among older respondents (OR, 0.2; 95% CI, 0.1–0.7; n = 3). Family history of cancer did not differ between schwannoma cases and controls, although the statistical power to detect associations was limited. Some relative risk estimates were based on a small number of observations and may have arisen by chance. Inheritance of predisposing genes, shared environmental factors, or both within families with a history of benign brain tumors, melanoma, or possibly breast cancer may be related to altered meningioma risk.